The Phenomenon of Presenting the Meaning of Verses in Quranic Content Instagram Review: The Practice of Living the Quran in Generation Z - Chindi Sri Hariyati; Amroeni Drajat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The development of social media has transformed the way religious messages, including the meaning of Qur’anic verses, are presented and received by Muslim society, especially Generation Z. One of the emerging phenomena is Qur’an review content on Instagram, which presents Qur’anic verses through simple, reflective, and contextual narratives. This study aims to analyze the presentation of Qur’anic meanings in Qur’an review content, examine how Generation Z interprets and responds to the content, and explain the phenomenon within the perspective of living Qur’an in digital space. This research employed a qualitative approach with a descriptive-analytic method and reception analysis. The data were collected through documentation techniques in the form of screenshots of 40 Qur’an review contents and audience comments on Instagram. The findings show that the presentation of Qur’anic meanings follows a consistent pattern consisting of life problems, presentation of verses, reflective explanation, internalization of meaning, and reinforcement of messages. Generation Z tends to interpret the content in reflective, emotional, and personal ways by relating the messages to their life experiences. Audience responses include emotional expressions, self-reflection, spiritual expressions, and religious discussions in the comment section. This study demonstrates that Qur’an review content can be understood as a form of digital living Qur’an practice, where the Qur’an is not only understood as a sacred text but also internalized, interpreted, and expressed through digital interaction.